Results of Intracytoplasmic Sperm Injection of Single Oocyte in 362 Unstimulated Cycles - Vlaisavljević, Veljko (Kluwer Academic Publishers-Plenum Publishers, 2002)
Purpose: The purpose was to test the adequacy of unstimulated cycles for intracytoplasmic sperm injection (ICSI) and to evaluate implantation and pregnancy rates in three different age groups. Methods: ICSI was performed in 362 unstimulated cycles in women up to 45 years old. All cycles were monitored by serum estradiol, urinary LH, and ultrasound. Results: The delivery rate per started cycle was higher in patients younger than 36 (9.4%) than in cycles with patient's age between 36 and 39 years (4.8%) or older than 40 (4.6%) but the difference was not statistically significant. In all groups, the fertilization rate was similar (70.4, 77.6, and 84.8%, respectively). The pregnancy rate per cycle and the pregnancy rate per puncture was similar in the group of patients in age between 36 and 39 years (8.3 and 9.7%) and those older than 40 (7.7 and 9.3%). Conclusions: Unstimulated cycles monitored by serum estradiol, urinary LH, and ultrasound can produce an acceptable pregnancy rate after ICSI procedure only in patients younger than 36.